Global Dissemination of Carbapenemase-Producing Klebsiella pneumoniae: Epidemiology, Genetic Context, Treatment Options, and Detection Methods - Lee, Chang-Ro; Lee, Jung Hun; Park, Kwang Seung; Kim, Young Bae; Jeong, Byeong Chul; Lee, Sang Hee (Frontiers in Microbiology, 2016)
The emergence of carbapenem-resistant Gram-negative pathogens poses a serious threat to public health worldwide. In particular, the increasing prevalence of carbapenem-resistant Klebsiella pneumoniae is a major source of concern. Klebsiella pneumoniae carbapenemases (KPC) and carbapenemases of the oxacillinase-48 (OXA-48) type have been reported worldwide. New Delhi metallo--lactamase (NDM) carbapenemases were originally identified in Sweden in 2008 and have spread worldwide rapidly. In this review, we summarize the epidemiology of K. pneumoniae producing three carbapenemases (KPCs, NDMs, and OXA-48-like). Although the prevalence of each resistant strain varies geographically, K. pneumoniae producing KPCs, NDMs, and OXA-48-like carbapenemases have become rapidly disseminated. In addition, we used recently published molecular and genetic studies to analyze the mechanisms by which these three carbapenemases, and major K. pneumoniae clones, such as ST258 and ST11, have become globally prevalent. Because carbapenemase-producing K. pneumoniae are often resistant to most -lactam antibiotics and many other non--lactam molecules, the therapeutic options available to treat infection with these strains are limited to colistin, polymyxin B, fosfomycin, tigecycline, and selected aminoglycosides. Although combination therapy has been recommended for the treatment of severe carbapenemase-producing K. pneumoniae infections, the clinical evidence for this strategy is currently limited, and more accurate randomized controlled trials will be required to establish the most effective treatment regimen. Moreover, because rapid and accurate identification of the carbapenemase type found in K. pneumoniae may be difficult to achieve through phenotypic antibiotic susceptibility tests, novel molecular detection techniques are currently being developed.